2012
DOI: 10.1258/ijsa.2009.009428
|View full text |Cite
|
Sign up to set email alerts
|

Social support mediates the relationship between HIV stigma and depression/quality of life among people living with HIV in Beijing, China

Abstract: SUMMARY Stigma toward people living with HIV is pervasive in China and related to poor service utilization, psychosocial distress, and diminished quality of life. In an effort to identify mechanisms to reduce HIV stigma and its negative consequences, we examined whether social support mediates the relation between enacted stigma and both depressive symptoms and quality of life among 120 HIV outpatients in Beijing, China. Generally, perceived social support was associated with less stigma, less depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
4
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 24 publications
11
109
4
7
Order By: Relevance
“…Qualitative research and quantitative studies can both make important contributions to the study of cultural influences on social support network and health outcome processes (as well as to the larger area of social support and health research). While quite a bit research in the area of social network support and health outcomes has been conducted in a variety of countries around the world, most of the research has been conducted in a relatively small number of countries in Europe and Asia (mainly China) (Van Tilburg, 1998;Sun et al, 2007;Deng et al, 2010;Rao et al, 2012).…”
Section: A Research Agenda For the Study Of Social Network Support Anmentioning
confidence: 99%
“…Qualitative research and quantitative studies can both make important contributions to the study of cultural influences on social support network and health outcome processes (as well as to the larger area of social support and health research). While quite a bit research in the area of social network support and health outcomes has been conducted in a variety of countries around the world, most of the research has been conducted in a relatively small number of countries in Europe and Asia (mainly China) (Van Tilburg, 1998;Sun et al, 2007;Deng et al, 2010;Rao et al, 2012).…”
Section: A Research Agenda For the Study Of Social Network Support Anmentioning
confidence: 99%
“…It is essential to deal with the internal stigma since it affects the individual's adherence to ART, quality of life, and their social experiences directly. 13,17,18,32 Steward et al 33 found that HIV-infected people on treatment who experience discrimination and who believe stigma against them are more likely to report symptoms of depression. In addition, experiences of discrimination and hearing stories about others being mistreated because of HIV correlate with the perception that stigma is more prevalent in the local community.…”
Section: Discussionmentioning
confidence: 99%
“…Dari hasil studi yang dilakukan oleh Rao et al (2012) di China menemukan bahwa stigma tinggi memiliki hubungan dengan gejala depresi dan menyebabkan kualitas hidup yang rendah. Selain itu, dukungan keluarga juga berkaitan dengan kesehatan fisik dan juga kesehatan mental pada populasi di dunia.…”
Section: Latar Belakangunclassified